Mapping Choroidal and Retinal Thickness Variation in Type 2 Diabetes using Three-Dimensional 1060-nm Optical Coherence Tomography - Esmaeelpour, Marieh; Považay, Boris; Hermann, Boris; Hofer, Bernd; Kajic, Vedran; Hale, Sarah L.; North, Rachel V.; Drexler, Wolfgang; Sheen, Nik J. L. (Investigative ophthalmology & visual science, 2011)
To map choroidal (ChT) and retinal thickness (RT) in healthy subjects and patients with diabetes with and without maculopathy using three dimensional 1060-nm optical coherence tomography (3D-1060nm-OCT). Sixty-three eyes from 42 diabetic subjects (41-82 years of age; 11 females) grouped according to a custom scheme using Early Treatment Diabetic Retinopathy Study definitions for pathology within 1 disc-diameter of fovea (without pathology [NDR], microaneurysms [M1], exudates [M2], clinically significant macular edema [CSME]) and 16 eyes from 16 healthy age matched subjects (38-79 years of age; 11 females) were imaged by 3D-1060nm-OCT performed over a 36° × 36° field of view. Axial length, 45° fundus photographs, body mass index, plasma glucose, and blood pressure measurements were recorded. The ChT at the subfoveal location and ChT maps between RPE and the choroidal-scleral interface were generated and statistically analyzed. RT maps show thinning in the NDR group but an increase in thickness with increasing maculopathy in the temporal and central regions (unpaired t-test; P < 0.05). ChT mapping of all diabetic patients revealed central and inferior thinning compared to healthy eyes (unpaired t-test; P < 0.001). Subfoveal ChT (mean ± SD) for healthy eyes was 327 ± 74 μm, which was significantly thicker than all diabetic groups (214 ± 55 μm for NDR, 208 ± 49 μm for M1, 205 ± 54 μm for M2, and 211 ± 76 μm for CSME (ANOVA P < 0.001; Tukey P < 0.001). 3D-1060nm-OCT has shown that the central choroid is thinner in all type 2 diabetic eyes regardless of disease stage. The choroidal thinning may exceed the magnitude of possible choriocapillaris atrophy. In contrast to the conventional assessment of pathologic thickness change in several locations, thickness maps allow investigation of the choroid over the extent of affected areas.